Inflammation, advancing age and nutrition research and clinical interventions (Academic Press, 2014)
The book provides a comprehensive overview to understanding the integrated impact of the concepts of cellular and molecular aspects, models, environmental factors, and lifestyle involved in premature aging. Additionally, it examines how functional food, dietary nutraceuticals or pharmacological compounds can reverse inflammation and premature aging based on personalized medicine. This book is a valuable resource for health professionals, scientists and researchers, nutritionists, health practitioners, students and for all those who wish to broaden their knowledge in the allied field.